Non-curative therapies and their impact on the prognosis of patients with myelodysplastic syndromes: a retrospective matched-pairs analysis - Rauhe, Katharina Anna; Kasprzak, Annika; Schulz, Felicitas; Nachtkamp, Kathrin; Strupp, Corinna; Kündgen, Andrea; Dietrich, Sascha; Mayer, Karin; Götze, Katharina S.; Hofmann, Wolf-Karsten; Giagounidis, Aristoteles; Gattermann, Norbert; et al. (Annals of hematology, 2025)
Allogeneic stem cell transplantation (SCT) remains the only curative therapy for patients with high-risk myelodysplastic syndromes (MDS). Due to age, comorbidities, or lack of urgency, many receive only palliative therapies to improve quality of life. Some patients remain untreated due to a lack of symptoms or low progression risk. Data on the impact of palliative therapies on overall survival (OS) and leukemia-free survival (LFS) are limited. Using the Düsseldorf MDS Registry, we compared outcomes of patients receiving red blood cell transfusions (RBCT) alone to the outcome of patients receiving RBCT combined with iron chelation therapy (ICT), erythropoietin (EPO), antithymoglobulin (ATG), or lenalidomide (LENA). Matched-pairs analysis was conducted using age, gender, and prognostic scores (Revised International Prognostic Scoring System or Chronic Myelomonocytic Leukemia-specific Prognostic Scoring System). ICT-treated patients (n = 85) had significantly improved OS (70 vs. 21 months, p < 0.001) and lower 5-year AML progression (3.5% vs. 28.2%, p < 0.001). Similar benefits were seen with EPO (n = 210; OS: 63 vs. 24 months, p < 0.001; AML: 5.7% vs. 19%, p = 0.007) and LENA (n = 30; OS: 92 vs. 57 months, p = 0.049; AML: 0% vs. 16.7%, p = 0.024). ATG (n = 11) showed no significant improvement in OS (79 vs. 64 months) or AML progression (0% vs. 18.2%). While recognizing the limitations of matched-pairs analysis versus randomized trials, our findings indicate a survival benefit from ICT, EPO, or LENA versus RBCT alone. The year of diagnosis did not independently affect OS or LFS. These results support the use of selected palliative therapies to improve long-term outcomes in MDS patients.